2004
DOI: 10.1016/j.rmed.2004.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Relief of dyspnoea by β2-agonists after methacholine-induced bronchoconstriction

Abstract: Virtually all asthma patients use brorichodilators. Formoterol and salbutamol have a rapid onset of bronchodilating effect, whereas salmeterol acts slower. We studied the onset of improvement of dyspnoea sensation after inhalation with these bronchodilators and placebo to reverse a methacholine-induced bronchoconstriction as a model for an acute asthma attack. Seventeen patients with asthma completed this randomised, double-blind, crossover, double-dummy study. On 4 test days, forced expiratory volume in 1 s (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
0
14
0
3
Order By: Relevance
“…Very-low-quality evidence (downgraded for risk of bias, imprecision, and indirectness) from 1 RCT 33 with 28 participants aged 3 months to 2 years showed benefit in reduction of respiratory rate (MD, 5.1; 95% CI, 0.45-9.75), wheezing score (MD, 0.8; 95% CI, 0.36-1.24), accessory muscle score (MD, 0.85; 95% CI, 0.45-1.23), and total clinical score (MD, 2.5; 95% CI, 1.06-3.94) when treatment (albuterol/salbutamol nebulization) was compared with placebo. Low-quality evidence (downgraded for imprecision and indirectness) from another RCT 34 with 17 participants aged 18 to 41 years showed benefit in reduction of time to subjective improvement in dyspnea in participants treated with fast-acting β 2 -adrenergic agonists (formoterol or salbutamol dry-powdered inhaler) compared with placebo dry-powdered inhaler or the slowacting β 2 -agonist (salmeterol dry-powdered inhaler). This study also demonstrated a reduction in time to return to baseline symptoms in the fast-acting β 2 -adrenergic agonist group compared with the placebo or slow-acting β 2 -agonist groups (MD indeterminable).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Very-low-quality evidence (downgraded for risk of bias, imprecision, and indirectness) from 1 RCT 33 with 28 participants aged 3 months to 2 years showed benefit in reduction of respiratory rate (MD, 5.1; 95% CI, 0.45-9.75), wheezing score (MD, 0.8; 95% CI, 0.36-1.24), accessory muscle score (MD, 0.85; 95% CI, 0.45-1.23), and total clinical score (MD, 2.5; 95% CI, 1.06-3.94) when treatment (albuterol/salbutamol nebulization) was compared with placebo. Low-quality evidence (downgraded for imprecision and indirectness) from another RCT 34 with 17 participants aged 18 to 41 years showed benefit in reduction of time to subjective improvement in dyspnea in participants treated with fast-acting β 2 -adrenergic agonists (formoterol or salbutamol dry-powdered inhaler) compared with placebo dry-powdered inhaler or the slowacting β 2 -agonist (salmeterol dry-powdered inhaler). This study also demonstrated a reduction in time to return to baseline symptoms in the fast-acting β 2 -adrenergic agonist group compared with the placebo or slow-acting β 2 -agonist groups (MD indeterminable).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Durch die Gabe von Bronchodilatatoren beim Asthma wird die Rückbildungszeit der Symptome bei Kindern verkürzt und bei jungen Erwachsenen die Anschlagszeit für die Verbesserung der Luftnot verringert [822,823]. Helfen Sie Asthmatikern mit akuten Atemproblemen bei der Einnahme ihrer bronchienerweiternden Therapie.…”
Section: Gabe Von Bronchodilatatorenunclassified
“…Both salbutamol and formoterol are known to reverse this contraction of airway smooth muscle that represents at least part of the component of airway obstruction occurring in an acute asthma exacerbation [1,2,26,27]. Two previous studies have shown that high-dose budesonide/formoterol was as effective and well tolerated in the treatment of acute asthma in an emergency setting as high-dose salbutamol [19] or high-dose formoterol [20].…”
Section: Discussionmentioning
confidence: 99%